Experimental Issues in Testing a Semiactive Technique to Control Earthquake Induced Vibration. (14th May 2014) - Caterino, Nicola; Spizzuoco, Mariacristina; Londoño, Julian M.; Occhiuzzi, Antonio
Abstract : This work focuses on the issues to deal with when approaching experimental testing of structures equipped with semiactive control (SA) systems. It starts from practical experience authors gained in a recent wide campaign on a large scale steel frame structure provided with a control system based on magnetorheological dampers. The latter are special devices able to achieve a wide range of physical behaviours using low-power electrical currents. Experimental activities involving the use of controllable devices require special attention in solving specific aspects that characterize each of the three phases of the SA control loop: acquisition, processing, and command. Most of them are uncommon to any other type of structural testing. This paper emphasizes the importance of the experimental assessment of SA systems and shows how many problematic issues likely to happen in real applications are also present when testing these systems experimentally. This paper highlights several problematic aspects and illustrates how they can be addressed in order to achieve a more realistic evaluation of the effectiveness of SA control solutions. Undesired and unavoidable effects like delays and control malfunction are also remarked. A discussion on the way to reduce their incidence is also offered.